BEHAVIORAL BIASES AND THEIR IMPACT ON INVESTMENT DECISION - AN ANALYTICAL STUDY ON A SAMPLE OF PRIVATE BANKS LISTED IN THE IRAQI STOCK EXCHANGE - Orooba Rashid Ali AL- Badran (Scholar Express Journals, 2022)
Financial organizations have become not only affected by decisions resulting from uncertainty, but also by behavioral biases. Thus, the main objective of the study is to find the effect of behavioral biases in the investment decision through an analytical study of private banks listed in the Iraqi Stock Exchange. After conducting field interviews and reviewing the reality of banks of the study sample, the data was collected through the use of a questionnaire distributed to (150) workers in those banks. Then, it was analyzed using the program (SPSS. 25). Based on the results of this study, a number of conclusions and suggestions were reached to fit the nature of the study
Keywords: Behavioral biases; Private banks; Investment decision; Iraqi Stock Exchange.